2015
DOI: 10.5194/bg-12-2831-2015
|View full text |Cite
|
Sign up to set email alerts
|

Drought-influenced mortality of tree species with different predawn leaf water dynamics in a decade-long study of a central US forest

Abstract: Abstract. Using decade-long continuous observations of tree mortality and predawn leaf water potential (ψpd) at the Missouri Ozark AmeriFlux (MOFLUX) site, we studied how the mortality of important tree species varied and how such variations may be predicted. Water stress determined inter-annual variations in tree mortality with a time delay of 1 year or more, which was correlated fairly tightly with a number of quantitative predictors formulated based on ψpd and precipitation regimes. Predictors based on temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 77 publications
2
72
0
Order By: Relevance
“…Thus, leaf abscission and stomatal closure are important mechanisms that reduce transpiration and minimize the risk of cavitation for temperate deciduous species (Federer 1980;Roberts et al 1980;Lucier and Hinckley 1982;Ginter-Whitehouse et al 1983;Gu et al 2007). Consistent with these findings, Gu et al (2015) observed greater mortality of drought-tolerant Q. alba and Q. rubra compared with other drought-sensitive and intolerant species (A. saccharum, F. americana) following an extreme drought in 2012, which was primarily associated with the lack of regulation of predawn water potential of the drought-tolerant species.…”
Section: Integrating Drought Tolerance and Sensitivitysupporting
confidence: 70%
See 2 more Smart Citations
“…Thus, leaf abscission and stomatal closure are important mechanisms that reduce transpiration and minimize the risk of cavitation for temperate deciduous species (Federer 1980;Roberts et al 1980;Lucier and Hinckley 1982;Ginter-Whitehouse et al 1983;Gu et al 2007). Consistent with these findings, Gu et al (2015) observed greater mortality of drought-tolerant Q. alba and Q. rubra compared with other drought-sensitive and intolerant species (A. saccharum, F. americana) following an extreme drought in 2012, which was primarily associated with the lack of regulation of predawn water potential of the drought-tolerant species.…”
Section: Integrating Drought Tolerance and Sensitivitysupporting
confidence: 70%
“…Quercus spp.) experienced higher mortality following an extreme drought year in the Midwestern USA as compared with presumably more drought intolerant species, Acer saccharum and Fraxinus americana (Gu et al 2015). The inconsistency in classification across studies presents a conundrum that plagues drought research: uncertainty in how we define tolerance and what criteria should be used to classify species in a reliable and meaningful way.…”
Section: Classification Of Drought Tolerance Of Northeastern Us Spementioning
confidence: 99%
See 1 more Smart Citation
“…Further, warmer temperatures in the absence of significant drought have been shown to increase tree growth rates, particularly in deciduous species (Way and Oren 2010). Overall, the direct mortality consequences of warming could be relatively small and limited when considered globally, as earth system feedbacks (e.g., greater atmospheric moisture and precipitation) combined with multiple treelevel compensatory processes can buffer future Xiong et al 2011, Kharuk et al 2013, Zhang et al 2014b, Zhou et al 2013, 2014bAustralasia, Semple et al 2010; Europe,Čater 2015; North America, Vogelmann et al 2009, Zegler et al 2012, Baguskas et al 2014, Hart et al 2014, Kane et al 2014, Twidwell et al 2014, Gu et al 2015South America, Brienen et al 2015. v www.esajournals.org tree mortality relative to hotter droughts (e.g., Klein et al 2014a).…”
Section: Temperaturementioning
confidence: 99%
“…It is common for species within the same ecosystem to employ opposing hydraulic strategies (e.g., risk prone or risk adverse; McCulloh et al, ; Ford et al, ). Disparities in transpiration volume and timing, due to differences in whole‐plant hydraulic strategies employed within the same forest, have important implications for forest growth and response to drought and disturbance (Roman et al, ; McDowell et al, ; Matheny et al, ; Gao et al, ; Gu, Pallardy, Hosman, & Sun, ; Wullschleger, Meinzer, & Vertessy, ). Several water flux studies have shown that many species of ring‐porous, anisohydric oak continue to transpire after other species curtail their water use during mild to moderate drought (e.g., von Allmen, Sperry, & Bush, ; Baldocchi & Xu, ; Hernandez‐Santana, Martinez‐Fernandez, Moran, & Cano, ; Matheny et al, ).…”
Section: Introductionmentioning
confidence: 99%